Harmony Among Family Members with Different Religions: Case Ngaju Dayak - NORMUSLIM, N. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In the perspective of conflict theory, family harmony is created due to coercion, both by the system and by the stronger groups to the weaker ones. Academically, the results of this study have a scientific contribution in order to enrich modern social theories as suggested by sociologists in functional, structural and conflict theory. In addition, it is also expected that the results of the study can give sufficient information to create an alternative way of reducing inter-religious conflicts in Indonesia. RESUMEN En la perspectiva de la teoría del conflicto, la armonía familiar se crea debido a la coerción, tanto por el sistema como por los grupos más fuertes a los grupos más débiles. Académicamente, los resultados de este estudio tienen una contribución científica para enriquecer las teorías sociales modernas como lo sugieren los sociólogos en la teoría estructural funcional y la teoría de conflictos. Además, también se espera que los resultados del estudio puedan proporcionar información suficiente para crear una forma alternativa de reducir los conflictos interreligiosos en Indonesia.